2019
DOI: 10.1002/gcc.22723
|View full text |Cite
|
Sign up to set email alerts
|

CRLF2 expression associates with ICN1 stabilization in T‐cell acute lymphoblastic leukemia

Abstract: T‐cell acute lymphoblastic leukemia (T‐ALL) is an aggressive hematopoietic malignancy with few molecular alterations showing a consensual prognostic value. CRLF2 overexpression was recently identified in high‐risk T‐ALL patients. For these cases, no genomic abnormality was found to be associated with CRLF2 overexpression. IKZF1 has been recently shown to be a direct transcriptional regulator of CRLF2 expression. Moreover, it is known that NOTCH1 antagonizes IKZF1 in T‐ALL. In light of these pieces of evidence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…We previously demonstrated that NOTCH1/FBXW7 mutations leading to stabilization of the NOTCH1 nuclear protein are associated with CRLF2 overexpression in T‐ALL 7 . In the present study, we found 15% of PTEN mutations in the CRLF2 ‐high subgroup (Figure 1A).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…We previously demonstrated that NOTCH1/FBXW7 mutations leading to stabilization of the NOTCH1 nuclear protein are associated with CRLF2 overexpression in T‐ALL 7 . In the present study, we found 15% of PTEN mutations in the CRLF2 ‐high subgroup (Figure 1A).…”
Section: Discussionsupporting
confidence: 67%
“…We previously demonstrated that NOTCH1/FBXW7 mutations leading to stabilization of the NOTCH1 nuclear protein are associated with CRLF2 overexpression in T-ALL. 7 In the present study, we found 15% of PTEN mutations in the CRLF2-high subgroup (Figure 1A). Noteworthy, NOTCH1 regulates PTEN expression and PTEN loss is associated with resistance to pharmacological inhibition of NOTCH1 in T-ALL.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In addition, KDM5B expression is downregulated by Ikaros through recruiting HDAC1 to the KDM5B gene promoter, which causes an inhibitory chromatin condition and transcriptional inhibition consequently ( Dhanyamraju et al, 2020 ). Ikaros upregulates the PHF2 expression through chromatin remodeling, as demonstrated by the appearance of increased H3K4me3 in the promoter of the PHF2 gene ( Ge et al, 2016a ; Ge et al, 2018a ; Maciel et al, 2019 ). The expression of ARID5B is positively adjusted by Ikaros, and the loss of a single copy of IKZF1 is associated with low ARID5B expression ( Ge et al, 2018b ).…”
Section: Ikaros Family Signalingmentioning
confidence: 99%